Confronting Terrorist Criminals in the Digital Space, A Glance at the Legislative Experience in Islamic Countries - Peyman Namamian; Fatemeh Ameri Siahoui (مطالعات تطبیقی حقوق کشورهای اسلامی)
With the increasing use of information and communication technology in various areas of contemporary life, widespread access to the Internet and the use of social media, individuals and organizations are faced with constant threats and challenges arising from the adverse consequences of terrorist crimes in the digital space. Terrorist crimes in the digital space are today referred to as crimes that are not limited to time, place and region and cause damage. Today, this category of electronic crimes is one of the main challenges for law enforcement. Information technology is faced with a wave of laws that protect the interests of people who use web technology. These laws are derived from common laws and regulations in general crimes. With the growth of digital technologies, the way in which this type of crime is committed in the digital space has expanded in a terrifying and extreme way, and while creating insecurity in this space for users, it has also provided the opportunity for terrorist crimes to be committed. As digital infrastructure becomes more critical and barriers to entry for malicious actors decrease, terrorist crimes in the digital space have become a growing concern. Detecting, responding to, and preventing this crime pose unique challenges for law enforcement and governments, requiring a multifaceted approach. Accordingly, this article seeks to identify this criminal phenomenon within the realm of prevailing policy in the legislative policy of Islamic countries, and to examine the possibility of confronting it in such a situation.